The Demographic Situation of Ageing Population in Nepal (Shanti Journal, 2023)
The title of the study is “Demographic Situation of Population Ageing in Nepal,” and its main objective is to illustrate and describe the population situation of ageing in Nepal. The population of old age people is increasing day by day which is a challenge for developing countries like Nepal. Due to this, I was curious to study the situation of the elderly people. The ageing trends and situation of older people are analyzed using the census data of 1952/54-2021AD. This article follows descriptive and analytical methods which are based on secondary sources of data. Furthermore, it is based on a literature review, books, journals, articles, and reports. All these are from internet sources. The age structure of the population in Nepal is in increasing trend. Over the years with declining fertility and controlled adult mortality, the old age population has been increasing. The population of elderly people in the country is increasing both in terms of absolute number and as the proportion of the total population which is growing faster than the annual population growth. Because of better healthcare facilities,  nutritious food, and awareness. The elderly people have more knowledge, experience, and wisdom. So, they are an asset to the nation. Society or nation can use these qualities of the elderly people in national reconstruction. With the gradual increase in life expectancy at birth and decline in mortality rate, the median age is in increasing trends. In the Nepalese context, the rate of growth in the elderly population surpasses that of the overall population.